Innate Immunity Evasion by Enteroviruses Linked to Epidemic Hand-Foot-Mouth Disease - Jin, Yuefei; Zhang, Rongguang; Wu, Weidong; Duan, Guangcai (Frontiers in Microbiology, 2018)
Enterovirus (EV) infections are a major threat to global public health, and are responsible for mild respiratory illness, hand, foot and mouth disease (HFMD), acute hemorrhagic conjunctivitis, aseptic meningitis, myocarditis, severe neonatal sepsis-like disease, and acute flaccid paralysis epidemic. Among them, HFMD is a common pediatric infectious disease caused by Enteroviruses of the family Picornaviridae including EV-A71, coxsackieviruses (CV)-A2, CV-A6, CV-A10 and CV-A16. Due to lack of vaccines and specific antiviral therapeutics, millions of children still suffer from HFMD. Innate immune system detects foreign invaders by means of a relatively limited number of sensors, such as pattern recognition receptors (PRRs) [eg. Retinoic Acid-Inducible Gene I (RIG-I)-like receptors (RLRs), Toll-like receptors (TLRs) and NOD-like receptors (NLRs)] and even some secreted functional proteins. However, a range of research, highlighted in this review, suggest that Enteroviruses-associated with HFMD have evolved different strategies to avoid detection by innate immunity via different proteases (eg. 2A, 3C, 2C, 3D). Ongoing efforts to better understand virus–host interactions that control innate immunity and then distill how that influences HFMD development, promises to have real-world significance. In this review, we address this complex topic in nine sections including multiple proteins associated with PRR and type I interferon (IFN) signaling. Recognizing how Enteroviruses linked to HFMD evade host innate immune system, we also describe the interactions between them and, finally, suggest future directions to better inform drug development and public health.